Performance and Security Analysis of Lightweight Hash Functions in IoT - Mufidah, Nada Fajri; Nuha, Hilal Hudan (Jurnal Informatika: Jurnal Pengembangan IT, 2024)
The rapid proliferation of Internet of Things (IoT) devices across various sectors, including healthcare, automotive, smart homes, and agriculture, has created a need for robust security measures that do not compromise the limited resources of these devices. This study analyses the performance and security of several lightweight cryptographic hash functions, specifically SHAKE128, BLAKE2s, SHA-256, SHA3-256, SipHash and xxHash, within the context of the Internet of Things (IoT). A series of experiments conducted on the Arduino Uno platform allows for an evaluation of these functions in terms of throughput, memory usage, and avalanche effect. The findings indicate that while SHAKE128 and SHAKE256 demonstrate superior throughput, they require greater memory, particularly with larger input sizes. BLAKE2s exhibits a robust equilibrium between throughput, memory efficiency, and consistent avalanche effects, rendering it a dependable option for 256-bit outputs. Conversely, xxHash and SipHash provide high throughput and minimal memory usage, yet exhibit reduced avalanche effects. The findings of this research provide critical insights for developers and researchers on the selection of appropriate cryptographic solutions, which must be tailored to the constraints and security requirements of IoT devices.